A Comparison of Rib Osteochondral Graft to Medial Femoral Trochlear Osteocartilaginous Graft for the Salvage of the Fragmented Scaphoid Proximal Pole: A Single-Center Experience with Minimum 2-Year Follow-Up - Butler, Stephen; Galbraith, John; Ek, Eugene T. H.; Berger, Anthony; McCombe, David; Tham, Stephen K. (Journal of Wrist Surgery, 2023)
Purpose Fragmented fractures of the proximal pole of the scaphoid that cannot be internally fixed may be salvaged by four-corner arthrodesis or proximal row carpectomy. Replacement of the proximal scaphoid with costal-osteochondral graft (COG) or the medial femoral trochlea (MFT) graft are two alternative solutions for this clinical presentation. The purpose of this study was to compare the clinical and radiographic results of the COG and the MFT graft with a minimum 2-year follow-up from a single centre.Methods A retrospective study was performed to investigate the outcome of COG and MFT with a minimum 2 year follow up. Demographic data and clinical assessment including wrist range of motion and grip strength measurements and Oxford Knee score were collected. Patients completed the outcome measures of Disabilities of Arm, Shoulder, and Hand (DASH), the Patient-Rated Wrist Evaluation (PRWE), and a ten-point visual analogue score for pain (VAS). Radiological examination was performed on all wrists at follow-up.Results The visual analogue score, DASH and PRWE were similar between the two groups. There was radiographic evidence of arthritis between the radial styloid and distal scaphoid in all patients that underwent COG but no evidence in those that underwent MFT graft reconstruction. There were different complications in each group. Thirty percent of patients that underwent MFT reconstruction had persistent knee pain at follow up.Conclusion Though there are notable differences in the follow-up period, patients undergoing MFT risk developing knee pain, while those undergoing COG risk radiographic progression of wrist arthritis.Level of Evidence III – Comparative study.
Keywords: scaphoid; proximal pole; costal-osteochondral; rib graft; medial femoral trochlea